The resource based view and the new competitive landscape: characterizing positions of dynamic capability - Medcof, John W.; McMaster University, Michael G. DeGroote School of Business, Management of Innovation and New Technology Research Centre (My University, 1998)
The resource-based view of the firm is extended by providing detailed, theory-based characterizations of the three categories of resources identified by Barney, and the organizational environment, to give a clearer understanding of the nature of position and the kind of organizational infrastructure needed to sustain dynamic capabilities.
36 leaves ; Includes bibliographical references (leaves 26-32). ;
Keywords: Resource allocation Corporate culture Strategic planning Organizational effectiveness